Incriminating vectors of deer malaria (Plasmodium odocoilei) at a Florida deer farm - Morgan Rockwell; Samantha M. Wisely; Derrick K. Mathias; Nathan D. Burkett-Cadena (Parasites & Vectors)
Abstract Background Plasmodium odocoilei, the only nonhuman Plasmodium parasite of native mammals in North America, infects white-tailed deer (WTD) throughout the eastern USA. Although deer malaria is not a significant cause of disease in healthy deer, infection with P. odocoilei may increase susceptibility to infection with and mortality due to epizootic hemorrhagic disease virus in deer fawns. The incrimination of the vector(s) of deer malaria is an essential step in developing management plans for reducing the incidence of deer malaria. Methods At a deer farm in Gadsden County, FL, with previously documented evidence of deer malaria transmission, mosquitoes were collected using carbon-dioxide-baited light traps, aspirators, and resting shelters. White-tailed deer host use and P. odocoilei infection rates were quantified in potential vector mosquito samples using polymerase chain reaction and Sanger sequencing. Results Diverse mosquito species (n = 38) were active at the deer farm. Four mosquito species or species complexes specialized in feeding on WTD were observed, taking at least 75% of blood meals from this one host species: Anopheles quadrimaculatus s.l. (88.9%), Anopheles punctipennis (83.3%), Anopheles crucians s.l. (81.4%), and Culex erraticus (87.7%). The highest infection rate of P. odocoilei was found in An. quadrimaculatus s.l. (4.1%), followed by An. punctipennis (3.1%), and An. crucians s.l. (0.47%). No other mosquito species were found to be infected with P. odocoilei. Conclusions Anopheles quadrimaculatus s.l., An. punctipennis, and An. crucians s.l. met three of the criteria for vector incrimination. These species were present in areas inhabited by WTD, specialized in feeding on WTD, and were naturally infected with P. odocoilei. Anopheles quadrimaculatus s.l. and Anopheles punctipennis are the most likely natural vectors of deer malaria in Florida, as indicated by their high percentages of WTD blood meals (> 83%) and relatively high infection rates (> 3%). To fully incriminate the vector(s) for P. odocoilei, laboratory vector competence studies are needed to determine their ability to biologically transmit the parasites. Graphical Abstract